Negative Chronotropic Cardiovascular Changes in Lumbar Spine Surgery: A Potential Spinal-Cardiac Reflex? - Sultan, Kashif Ali; Ashraf, Mohammad; Chaudhary, Attika; Al Salloum, Laulwa; Ghulam, Naseeruddin; Ahmed, Nazir; Ismahel, Hassan; Farooq, Minaam; Iqbal, Javed; Ashraf, Naveed (Asian Journal of Neurosurgery, 2023)
Cardiovascular changes following lumbar spine surgery in a prone position are exceedingly rare. Over the past 20 years, a total of six cases have been published where patients experienced varying degrees of bradycardia, hypotension, and asystole, which could be attributed to intraoperative dural manipulation. As such, there is emerging evidence for a potential neural-mediated spinal-cardiac reflex. The authors report their experience of negative chronotropy during an elective lumbar spine surgery that coincided with dural manipulation and review the available literature. A 34-year-old male presented with a long-standing history of lower back pain recently deteriorating to bilaterally radiating leg pain, with restricted left leg raise, and numbness at the left L5 dermatomal territory. The patient was an athletic police officer with no comorbidities or past medical history. Magnetic resonance imaging lumbosacral spine revealed spinal stenosis most pronounced at L4/L5 and disc bulges at L3/L4 and L5/S1. The patient opted for lumbar decompression surgery. After an unremarkable comprehensive preoperative workup, including cardiac evaluation (electrocardiogram, echocardiogram), the patient was induced general anesthesia in a prone position. A lumbar incision was made from L2 to S1. When the left L4 nerve root was retracted while removing the prolapsed disc at L4/L5, the anesthetist cautioned the surgeon of bradycardia (34 beats per minute [bpm]), and the surgery was immediately stopped. The heart rate improved to 60 bpm within 30 seconds. When the root was later retracted again, a second episode of bradycardia occurred for 4 minutes with heart rate declining to 48 bpm. The surgery was stopped, and after 4 minutes, the anesthetist administered 600 µg of atropine. The heart rate then rose to 73 bpm within 1 minute. Other potential causes for bradycardia were excluded. The total blood loss was estimated to be 100 mL. He remains well at his 6-month follow-up and has returned to work as normal. Akin to previously published cases, each episode of bradycardia coincided with dural manipulation, which may indicate a possible reflex between the spinal dura mater and the cardiovascular system. Such a rare adverse event may occur even in seemingly healthy, young individuals, and anesthetists should caution the operating surgeon of bradycardias to exclude operative manipulation of the dura as the cause. While this phenomenon is only reported in a handful of lumbar spine surgery cases, it provides evidence for a potential spinal-cardiac physiological reflex in the lumbar spine that may be neural mediated and should be investigated further.
Keywords: bradycardia; negative chronotropy; lumbar spine; mechanism; spinal-cardiac reflex